2021
DOI: 10.1107/s1600577521007025
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of XANES and EXAFS for local structural characterization of disordered metal oxides

Abstract: In functional materials, the local environment around active species that may contain just a few nearest-neighboring atomic shells often changes in response to external conditions. Strong disorder in the local environment poses a challenge to commonly used extended X-ray absorption fine structure (EXAFS) analysis. Furthermore, the dilute concentrations of absorbing atoms, small sample size and the constraints of the experimental setup often limit the utility of EXAFS for structural analysis. X-ray absorption n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…, the damage caused to electrochemical devices. In turn, the more complex, in terms of the experimental setups and the interpretation of the results, and more recently developed methods—transmission electron microscopy, 26 scanning probe microscopy, 27,28 X-ray absorption fine structure (EXAFS), 29 etc. —are well-suited for studying thin films and interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, the damage caused to electrochemical devices. In turn, the more complex, in terms of the experimental setups and the interpretation of the results, and more recently developed methods—transmission electron microscopy, 26 scanning probe microscopy, 27,28 X-ray absorption fine structure (EXAFS), 29 etc. —are well-suited for studying thin films and interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…23 Imaging techniques such as scanning electron microscopy 24,25 or even X-ray tomography 7 are useful for assessment of the consequences of chemical expansion, e.g., the damage caused to electrochemical devices. In turn, the more complex, in terms of the experimental setups and the interpretation of the results, and more recently developed methods-transmission electron microscopy, 26 scanning probe microscopy, 27,28 X-ray absorption ne structure (EXAFS), 29 etc.are well-suited for studying thin lms and interfaces. 10 Various original combinations of methods, e.g., Raman spectroscopy coupled with electrochemical titration 30 and time-resolved XRD coupled with potential step chronoamperometry, 31 regularly emerge, allowing previously inaccessible insights into chemical strain to be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…Cosine similarity scores are defined as cos() = A Á B = kAk kBk, where A (or B) refer to the vectors from the origin to the point of each sample in the principal subspace. Based on their cosine similarity score, XANES spectra are divided into three groups for Ti species: region I (1%, 8% and 19% Ti-GDC), transition region [28% Ti-GDC, 38% Ti-GDC reproduced from Li et al (2021)] and region II (57%, 65%, 74%, 84% and 88% Ti-GDC). This grouping is consistent with the results obtained by Ce species, as shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Ti oxide/20GDC (Makagon et al, 2022(Makagon et al, , 2021 (denoted as Ti-GDC for brevity) nanocomposites are found to be integral components functioning as WBs in ECM actuation. The local environment of the Ti species was reported to be a distorted TiO 6 octahedron in the case of 38% Ti in Ti-GDC (Li et al, 2021). In addition, the dimensional changes under an external electric field were shown to be related to the ordering/disordering structural changes of the TiO 6 octahedron (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 97%
“…To obtain atomic-level structural information, we previously employed X-ray absorption spectroscopy (XAS) to characterize transition metal catalysts in both ex-situ and in-situ/operando studies. , Specifically, the extended X-ray absorption fine structure (EXAFS) analysis can provide valuable insights into the local geometric structure and coordination environment of the metal sites. The X-ray absorption near edge structure (XANES) spectra are particularly sensitive to the electronic structure of the metal center and its local environment. Our recent work utilized XANES spectra of CoX/C 3 N 4 to probe possible intermediates during photocatalytic CO 2 reduction. While the chemometrics-based approach for separating between different Co structures coexisting in reaction conditions was successful, the choice of the structural model for using a machine learning – based method of XANES data analysis was guided by human expertise only.…”
Section: Introductionmentioning
confidence: 99%